The effect of microbiome-modulating therapeutics on glucose homeostasis in metabolic syndrome: A systematic review, meta-analysis, and meta-regression of clinical trials - Ridhima Kaul (12485902) (2024)
Background Metabolic syndrome (MetS) is a chronic disorder featuring overweight/obesity, high blood pressure, and dysfunction of lipid and carbohydrate metabolism. Microbiome-modulating probiotics, prebiotics, synbiotics and fecal microbiota transplant (FMT) are promising adjunct therapies for improving parameters of glucose homeostasis and insulinemia. Methods We conducted a comprehensive systematic review, meta-analyses, and meta-regressions to investigate the effect of the abovementioned microbiome therapies on various biomarkers after screening clinical trials published through April 2023. We pooled data using random effects meta-analyses, reporting them as mean differences (MDs) with 95 % confidence intervals (CIs), and conducting univariate linear model meta-regressions. Results Data from 21 trial comparisons across 19 studies (n = 911) revealed that, compared to placebo/control, microbiome-modulating therapies were associated with statistically significant changes in fasting plasma glucose (MD: 4.03 mg/dL [95%CI: 6.93; −1.13]; peffect = 0.006, I2 = 89.8 %), and fasting insulin (MD: 2.56 μU/mL [95%CI: 4.28; −0.84]; peffect = 0.004, I2 = 87.9 %), but not insulin resistance or sensitivity indices and HbA1c. Age, baseline BMI, baseline biomarker value, pro/synbiotic dosage, trial duration, nutraceutical type, and WHO region were factors affecting the efficacy of these interventions at producing changes in biomarkers, signaling the potential role of personalized precision medicine adjunct therapy for deranged glucose homeostasis in patients with MetS. Nevertheless, presence of heterogeneity calls for further investigation before their clinical application. Conclusions Probiotics, prebiotics, synbiotics and FMT supplementation improved fasting glucose and insulin in patients with MetS. Further large-scale and high-quality trials are required before potential clinical applications. Other Information Published in: Diabetes & Metabolic Syndrome: Clinical Research & Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.dsx.2024.103118